Pygocephalomorph Crustacea. New Data and Interpretations, with Emphasis on Brazilian and South Africa Forms. - PINTO, IRAJÁ DAMIANI; ADAMI-RODRIGUES, KAREN (Pesquisas em Geociências, 1996)
New data on Pygocephalomorph Crustacea is provided, together with a historical analysis of previous work on the group. Pygaspis brasiliensis Beurlen, 1934, from the Permian Iratí Formation of Brazil is redescribed and compared with South African pygocephalomorphs.